Psilocybin as a disease-modifying drug$aa salutogenic approach in psychiatry : medicine - Spangemacher, Moritz; Mertens, Lea Julia; Färber, Luca; Jungaberle, Andrea; Jungaberle, Henrik; Gründer, Gerhard (Deutsches Ärzteblatt, 2024)
In Germany, the treatment of people with mental disorders is provided in more than 400 psychiatric and 250 psychosomatic clinics, with around 55 000 and 11 000 beds, respectively. The annual number of cases totals almost one million and has more than...
Im Anhang ist auf den Seiten I-III, A-B ergänzendes Material
Gesehen am 22.04.2025